KETERAMPILAN MENYIKAT GIGI ANAK AUTISME TERHADAP DEBRIS INDEX SEKOLAH INKLUSI GALUH HANDAYANI SURABAYA - Dewi Diah Permatasari, Ni Kadek; Kusuma Astuti N.P, I.G.A; Fitria Ulfah, Siti; Hadi Sugito, Bambang (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
Oral health in children with autism remains a concern because limited toothbrushing skills may increase the debris index. This study aimed to analyze the effect of tooth brushing skill on the debris index among children with autism at Galuh Handayani Inclusive School, Surabaya. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of 41 first and second grade students, while 30 children with autism were selected using purposive sampling. The research instruments included a tooth brushing skill observation checklist and a debris index assessment form. Data were analyzed using the Wilcoxon Signed Rank test. The results showed that before the intervention, 60% of participants had a poor debris index, whereas after the intervention all participants (100%) achieved a good category. The Wilcoxon test yielded a p value of 0.000, indicating a statistically significant difference in debris index before and after the intervention. It can be concluded that tooth brushing skill significantly reduced the debris index and improved oral health among children with autism.